Business, politics, and the state in Africa challenging the orthodoxies on growth and transformation - Kelsall, Tim 1970-; Booth, David 1945-; Cammack, Diana; Cooksey, Brian; Gebremichael, Mesfin; Golooba-Mutebi, Fred; Vaughan,Sarah (Zed Books, 2013)
Drawing on studies of Rwanda, Ethiopia, Tanzania and Ghana this book provides a new theory of the polticial and institutional conditions required for growth in Africa.